Developmental endothelial locus-1 attenuates palmitate-induced apoptosis in tenocytes through the AMPK/autophagy-mediated suppression of inflammation and endoplasmic reticulum stress. Issue 12 (1st December 2022) - Park, Tae Jun; Park, Seung Yeon; Cho, Wonjun; Oh, Heeseung; Lee, Hyun Jung; Abd El-Aty, A. M.; Bayram, Cemil; Jeong, Ji Hoon; Jung, Tae Woo
Abstract : Aims: Myokine developmental endothelial locus-1 (DEL-1) has been documented to alleviate inflammation and endoplasmic reticulum (ER) stress in various cell types. However, the effects of DEL-1 on inflammation, ER stress, and apoptosis in tenocytes remain unclear. Methods: Human primary tenocytes were cultured in palmitate (400 μM) and palmitate plus DEL-1 (0 to 2 μg/ml) conditions for 24 hours. The expression levels of ER stress markers and cleaved caspase 3, as well as phosphorylated 5' adenosine monophosphate-activated protein kinase (AMPK) and autophagy markers, were assessed by Western blotting. Autophagosome formation was measured by staining with monodansylcadaverine, and apoptosis was determined by cell viability assay and caspase 3 activity assay. Results: We found that treatment with DEL-1 suppressed palmitate-induced inflammation, ER stress, and apoptosis in human primary tenocytes. DEL-1 treatment augmented LC3 conversion and p62 degradation as well as AMPK phosphorylation. Moreover, small interfering RNA for AMPK or 3-methyladenine (3-MA), an autophagy inhibitor, abolished the suppressive effects of DEL-1 on inflammation, ER stress, and apoptosis in tenocytes. Similar to DEL-1, 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR), an activator of AMPK, also attenuated palmitate-induced inflammation, ER stress, and apoptosis in tenocytes, which 3-MA reversed. Conclusion: These results revealed that DEL-1 suppresses inflammation and ER stress, thereby attenuating tenocyte apoptosis through AMPK/autophagy-mediated signalling. Thus, regular exercise or administration of DEL-1 may directly contribute to improving tendinitis exacerbated by obesity and insulin resistance. Cite this article: Bone Joint Res 2022;11(12):854–861.